2020
DOI: 10.2147/dmso.s248112
|View full text |Cite
|
Sign up to set email alerts
|

<p>Reduced Beige Adipogenic Potential in Subcutaneous Adipocytes Derived from Obese Chinese Individuals</p>

Abstract: Thermogenesis function has made brown/beige adipocyte an attractive target for obesity. Human brown adipose tissue activity is impaired in obesity in vivo. The present study aims to compare the differences in beige adipocyte differentiation potential of subcutaneous adipose tissue derived from normal weight and obese Chinese individuals in vitro. Methods: Adipose-derived stem cells (ADSCs) isolated from subcutaneous fat tissues of normal weight (NW) and obese (OB) groups were induced to differentiate into matu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Furthermore, adipocytes differentiated from subcutaneous abdominal WAT derived from obese individuals had lower UCP1 protein levels than that from lean persons [ 183 ]. Another report indicated that brown adipogenic potentials, such as thermogenic gene expression, oxygen consumption rate, and lipolysis ability, were impaired in preadipocytes isolated from subcutaneous fat tissues of obese individuals [ 184 ]. Although gender differences in the prevalence of BAT are still controversial, the thermogenic response to cold exposure was greater in females than in males, implying that sex steroids might contribute to different thermogenic processes [ 185 , 186 , 187 ].…”
Section: Obesity and Mitochondrial Metabolismmentioning
confidence: 99%
“…Furthermore, adipocytes differentiated from subcutaneous abdominal WAT derived from obese individuals had lower UCP1 protein levels than that from lean persons [ 183 ]. Another report indicated that brown adipogenic potentials, such as thermogenic gene expression, oxygen consumption rate, and lipolysis ability, were impaired in preadipocytes isolated from subcutaneous fat tissues of obese individuals [ 184 ]. Although gender differences in the prevalence of BAT are still controversial, the thermogenic response to cold exposure was greater in females than in males, implying that sex steroids might contribute to different thermogenic processes [ 185 , 186 , 187 ].…”
Section: Obesity and Mitochondrial Metabolismmentioning
confidence: 99%
“…Beige adipocytes lose UCP1 expression and mitochondrial density without persistent stimulation [ 71 ]. The expression of beige genes in subcutaneous fat is dysregulated in obese individuals [ 72 , 73 , 74 ]. In addition, there are methodological limitations in evaluating the activity of beige adipocytes in humans [ 56 ].…”
Section: Adipose Tissuementioning
confidence: 99%
“…Most of the data regarding hBAT activity come from populations with obesity [ 9 , 10 , 14 ], which can not determine the causal relationship between inactive BAT and obesity (i.e., whether defective BAT contributes to obesity or vice-versa). Hence, the present study aimed to detect the browning capacity of subcutaneous WAT in overweight individuals and explore if the sympathetic-induced browning potential of subcutaneous WAT changes at a pre-obesity stage.…”
Section: Discussionmentioning
confidence: 99%